HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DAN KOORDINASI MATA-TANGAN DENGAN AKURASI SERVIS ATAS BOLA VOLI PEMAIN SMAN 1 SENTAJO RAYA - Rahmad Gusranda; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on researcher’s observation at the field, when the players did training and inter-school match, most of them did overhand serve. When doing a punch, the ball mostly got out of the field, sometimes got stuck on the net or hit the net, even could not reach the opponent’s field, it meant that the overhand serve that was done by the player was not on target or the accuracy of their overhand serve was still low. The purpose of this research is to find out the relationship between the strength of arm muscle and shoulder, eye-hand coordination simultaneously and the volleyball players’ overhand serve accuracy of senior high school 1 Sentajo Raya. The population of this research was the volleyball team of senior high school 1 Sentajo Raya who were registered or actively followed the training in total 12 members. Considering the total of population was fewer than 100 people, so all of the population became the sample (total sampling) which is 12 people. The instruments that used in this research were expanding dynamometer, throw-catch the wall, and serve accuracy. The data gotten was analyzed by using product-moment correlation. The results gotten are the strength of arm muscle and shoulder does not have any relationship with overhand serve accuracy of volleyball team at senior high school 1 Sentajo Raya. Moreover, the eye-hand coordination does not have any relationship with overhand serve accuracy of volleyball team at senior high school 1 Sentajo Raya. Therefore, the researcher concludes that there is no relationship between the strength of arm muscle and shoulder, eye-hand coordination and overhand serve accuracy of volleyball team at senior high school 1 Sentajo Raya.Key Words: Strength of arm muscle and shoulder, eye-hand coordination, overhand serveaccuracy